Related party transactions and audit fees: the role of the internal audit function - Al-Dhamari, Redhwan Ahmed; Al-Gamrh, Bakr; Ku Ismail, Ku Nor Izah; Saad @ Ismail, Samihah (Springer International Publishing AG, 2017)
Related party transactions (RPTs) are viewed as genuine transactions that rationally fulfil other economic demands of a company.However, RPTs can also be used to transfer wealth from minority shareholders to controlling shareholders.The existence of such transactions may deteriorate financial reporting quality, increase audit risk, and as a result increase audit fees.This study examines the relationship between RPTs and audit fees in Malaysia, where ownership is often concentrated within a controlling family and corporate governance mechanisms are poor.It also investigates the moderating effect of the internal audit function (IAF) on this relationship.We find that external auditors base their fees on the types of RPTs undertaken. Specifically, our results show that audit fees are higher for firms that undertake RPTs involving the sale and purchase of assets, goods, and services.We also document that external auditors rely on the IAF, and thus their fees are lower for firms that undertake RPTs and that have made a large investment in an IAF. Our study is the first to provide evidence that RPTs in Malaysian firms may be abused as a channel to facilitate tunnelling and that the IAF plays a vital role in controlling such transactions.